Medición de desigualdades en salud: vacunación contra COVID-19 en Honduras año 2021 - Isaac Jonathan Marriaga Hernández (Revista Médica Hondureña, 2023)
Background: In vaccination, a health inequality is considered when vaccination coverage in a country presents differences between socially determined regions. Objective: To measure health inequalities in anti-COVID-19 vaccination coverage with two doses in the departments of Honduras, 2021. Methods: Quantitative, ecological study based on measurement of inequalities. Population unit consisted of 18 departments of Honduras. The health variable was the coverage of anti-COVID-19 vaccination with two doses, year 2021, obtained from the bulletin of the Ministry of Health of Honduras. The social variable was the population living in multidimensional poverty from the United Nations Development Program report, year 2022. Results: The absolute inequality gap showed a difference in vaccination coverage of -7.3 percentage points between the quartile of poorest and least poor departments. The relative gap, with a ratio of 0.87, showed that the departments in the poorest quartile had coverage that was 13% lower than the coverage of the least poor quartile. The slope inequality index was 0.19 percentage points, with a regression line with horizontality. The inequality concentration index was 2%, with a curve distributed over the equity line in 16 departments. Discussion: Anti-COVID-19 vaccination coverage in Honduras in 2021 met the target established by international guidelines and was achieved without disproportionate health inequalities, i.e. coverage was achieved with equity.